Diagnostic and Management Approach of Pancreatic Pseudocyst in Children - Nugraha, Marcel Aditya; Gayatri, Pramita (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2024)
Background: Pancreatic pseudocyst is a fluid-filled sac within the pancreas encapsulated by fibrous tissue. Blunt-abdominal trauma is the leading risk factor in children. Due to varied and non-specific clinical manifestations, diagnosis can be challenging. Thus, this study aimed to explain the diagnostic and management approach of pediatric pancreatic pseudocyst. Case: An 8-year-old boy presented with a 3-month history of progressive abdominal mass accompanied by abdominal pain, bilious vomiting, constipation, and weight loss. Physical examination revealed a skin-colored mass located in the epigastric region. A CT-scan confirmed a cystic lesion with well-defined borders in the pancreas. Laboratory tests indicated elevated levels of plasma amylase and lipase enzymes. The patient underwent endoscopic ultrasound (EUS), followed by cyst drainage. Analysis of the pseudocyst fluid revealed increased amylase and lipase enzymes, and carbohydrate antigen 19-9 (CA 19-9) levels. Discussion: A thorough patient history and physical examination are essential in diagnosing pancreatic pseudocyst. While CT-scan provides valuable information, EUS has higher sensitivity and specificity for diagnosis. Amylase and lipase enzymes levels are frequently elevated, and CA-19-9 can be useful, however, should be complemented with other biomarkers. Drainage is indicated for cysts that do not resolve spontaneously. Adequate nutrition is also crucial for successful patient management. Conclusion: Pancreatic pseudocysts should be considered in children with an abdominal mass following blunt-abdominal trauma. Endoscopic ultrasound (EUS) is a valuable tool for both diagnosing and assisting the management of pancreatic pseudocysts.